Role of hypothalamic de novo ceramides synthesis in obesity and associated metabolic disorders - Christophe Magnan; Hervé Le Stunff (Elsevier, 2021)
Background: Sphingolipid-mediated signalling pathways are described as important players in the normal functioning of neurons and nonneuronal cells in the central nervous system (CNS). Scope of review: This review aims to show role of de novo ceramide synthesis in the CNS in controling key physiological processes, including food intake, energy expenditure, and thermogenesis. The corollary is a condition that leads to a dysfunction in ceramide metabolism in these central regions that can have major consequences on the physiological regulation of energy balance. Major conclusions: Excessive hypothalamic de novo ceramide synthesis has been shown to result in the establishment of central insulin resistance, endoplasmic reticulum stress, and inflammation. Additionally, excessive hypothalamic de novo ceramide synthesis has also been associated with changes in the activity of the autonomic nervous system. Such dysregulation of hypothalamic de novo ceramide synthesis forms the key starting point for the initiation of pathophysiological conditions such as obesity - which may or may not be associated with type 2 diabetes.